The Sacred Insence: The Ketoret - קְטֹ֣רֶת - Robijaona Rahelivololoniaina Baholy (Matondang Journal, 2024)
Jewish religious traditions detailed in Exodus 30:34-38. Comprising rare spices like stacte, onycha, galbanum, and frankincense, the Ketoret (קְטֹ֣רֶת) was historically burned in the Tabernacle, symbolizing a direct connection to the divine. Despite ongoing debates on ingredient identification, the ritualistic importance of the Ketoret remains deeply rooted in Judaism, prompting continued exploration in religious scholarship, despite its absence in modern Jewish tradition. Our research conducts a thorough bibliographic review, integrating biblical data to scrutinize the complex phenomena surrounding the Ketoret. Seeking to provide innovative frameworks, our study aims to illuminate the ritual's intricacies, fostering paradigm shifts in interdisciplinary discourse and advancing scientific understanding. The burning of the sacred Ketoret, composed of Commiphora myrrha, Onycha, Ferula galbaniflua, and Boswellia sacra, transcends mere fragrance, symbolizing a transformative process. The rising smoke becomes a spiritual offering, creating a bridge between the terrestrial and celestial realms and mirroring the worshipper's ascent toward the divine. This study underscores the Ketoret's theological significance as a conduit for spiritual elevation and connection, where the burning ritual signifies a fragrant communion with the divine. Each ingredient's meticulous selection imparts layers of symbolic significance, representing unity and diversity within the divine fabric. The research also traces the historical evolution of aromatic practices, from traditional fumigation to contemporary extraction methods, highlighting enduring global traditions and diverse applications in various temples and Israel's Ministry of Health-approved kits.